Examining the impact of differential electricity pricing on industrial development: Evidence from panel VAR - Nada Fadl (Institute of Energy Economics at the University of Cologne (EWI), 2026)
Significant discrepancies in electricity pricing are observed across countries, particularly between industrial and household rates. Although the literature studies the relationship between electricity prices and economic performance, little empirical evidence exists on how electricity price differentiation between households and industry affects industrial development across countries. This paper addresses this gap by examining the dynamic relationship between industrial development and cross-subsidy electricity price structures. Using panel vector autoregression (VAR) for 17 OECD countries over a period of 25 years, the study assesses the impact of the electricity price ratio (households to industry) on industrial development. To capture the relative price structure between sectors, the analysis incorporates a cross-subsidy electricity price ratio, which reflects differences in electricity pricing across consumer groups. This ratio captures the joint effect of lower industrial production costs and higher household price incentives, thereby reflecting an industry-friendly economic or regulatory environment that supports industrial activity. The analysis is conducted for the full sample as well as various sub-samples. Orthogonalized impulse-response functions are estimated to disentangle the basic factors, such as capital and labor, from the effects of electricity prices on industrial development. The analysis distinguishes between the direct effect of industrial electricity prices on industrial development and an indirect effect operating through the relative electricity price structure. Consistent with existing literature, the results confirm the negative effect of industrial electricity price levels on industrial development. In addition, the results reveal a previously unexplored ratio effect, providing evidence that lower electricity prices for industry relative to households positively affect industrial development in OECD countries. Thus, the results indicate pricing structures that favor production firms and manufacturers. The findings further emphasize the importance of electricity price differentiation between the industry and households, particularly in the context of trade openness.
Keywords: C33; Q43; L94; L60; 330; Electricity price ratio; industrial development; panel vector autoregression